A Highly Efficient New T1 MRI Contrast Agent with r2/r1 ≈ 1.0: Mixed Cu(II)/Gd(III) Oxide Nanoparticle. (17th March 2015) - Bony, Badrul Alam; Baeck, Jong Su; Chang, Yongmin; Bae, Ji Eun; Chae, Kwon Seok; Lee, Gang Ho
<x xml:space="preserve">Abstract</x> An ideal T1 MRI contrast agent should have a large r1 value and r2/r1 ratio, which is close to 1. In this study, a new approach to accomplish this is presented using the mixed Cu(II)/Gd(III) oxide nanoparticle. The d‐glucuronic acid‐coated Cu(II)/Gd(III) oxide nanoparticle showed r1 = 13.78 mM−1 s−1 and r2 = 14.48 mM−1 s−1 (r2/r1 = 1.05). This result is due to reduced magnetization of mixed nanoparticle resulting from mixing of nearly nonmagnetic Cu(II) into the nanoparticle. This result shows that the d‐glucuronic acid–coated Cu(II)/Gd(III) oxide nanoparticle is a potential T1 MRI contrast agent.